Business students, the business world and reliable management: how far or how close are they to acquaintance with ethical and sustainable leadership? - Duarte de Almeida, I. (The 30th EurOMA Conference: A Systems Lens on Operations, 2023)
Business students' (BS) ethical maturity, decisions, and beliefs concerning Business Ethics (BE), Sustainable Operations (SO), and sustainability dilemmas were examined in coursework case studies. None of the students had ever taken BE or SO courses. Also, 100 Portuguese managers were surveyed about sustainability priorities and perceptions of BS skills needs in sustainability dilemmas, SO, and BE. Using the Global Reporting Initiative's (GRI)1 G4 reporting framework, sustainability dimensions were incorporated into the questionnaire. Research shows that BS are ethically mature but unaware of BE/SO research's importance. Globally, managers place the most emphasis on the economic dimension when considering BS skills needs.